Religious Beliefs and Political Practices. The Ethics of Conviction in the Militancy of MIRA Political Movement in Santiago de Cali - Bastidas Meneses, Luis Bernardo (Sociedad y Economía, 2013)
Unlike other political-electoral organizations associated with religious communities inColombia, the MIRA Political Movement has managed to mobilize a broad electoral base,forming a group of members who work on a permanent basis. This militancy is not onlypolitical but also religious, because it is part of the membership of one of the largest non-Catholic Christian churches in the nation. Thus, this research aims to show the influenceof religious beliefs in shaping this political militancy, analyzing through an ethnographicand documentary work, their political practices and religious beliefs, whose mutual relationshiphas become an ethics of Conviction.